Experimental and theoretical characterisation of rhodium-doped barium titanate - Corner, L; RamosGarcia, R; Petris, A; Damzen, M (1997)
We present the results of an experimental and theoretical investigation of the properties of rhodium-doped barium titanate (Rh:BaTiO3). In our theoretical analysis we derive an expression for the effective trap density in the three-valence state model, for the first time to our knowledge. We apply this model of photorefraction to the three-valence states of rhodium in Rh:BaTiO3, together with additional iron centres, and using this theory and our experimental results we deduce the population densities and some photorefractive parameters of Rh:BaTiO3. © 1997 Elsevier Science B.V.